2006
DOI: 10.1074/jbc.m508799200
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Effects of Oxidized Low Density Lipoprotein and α-Tocopherol on CD36 Scavenger Receptor Expression in Monocytes

Abstract: Vitamin E deficiency increases expression of the CD36 scavenger receptor, suggesting specific molecular mechanisms and signaling pathways modulated by ␣-tocopherol. We show here that ␣-tocopherol down-regulated CD36 expression (mRNA and protein) in oxidized low density lipoprotein (oxLDL)-stimulated THP-1 monocytes, but not in unstimulated cells. Furthermore, ␣-tocopherol treatment of monocytes led to reduction of fluorescent oxLDL-3,3-dioctadecyloxacarbocyanine perchlorate binding and uptake. Protein kinase C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 100 publications
1
100
0
3
Order By: Relevance
“…Several studies have shown the central role of CD36 in the development of atherosclerotic plaques by increasing the cellular uptake of modified LDL (9,10,19,21). CD36 expression is often increased at the atherosclerotic lesion by triggers such as oxLDL via PKB and PPARg activation (21). Interestingly, oxLDL has also been shown to inhibit the proteasome (63) and increased levels of ubiquitinated proteins and decreased proteasome activity were detected in unstable atherosclerotic plaques (12,64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the central role of CD36 in the development of atherosclerotic plaques by increasing the cellular uptake of modified LDL (9,10,19,21). CD36 expression is often increased at the atherosclerotic lesion by triggers such as oxLDL via PKB and PPARg activation (21). Interestingly, oxLDL has also been shown to inhibit the proteasome (63) and increased levels of ubiquitinated proteins and decreased proteasome activity were detected in unstable atherosclerotic plaques (12,64).…”
Section: Discussionmentioning
confidence: 99%
“…Extracts were prepared as previously described (21,22). Briefly, THP-1 cells were harvested by centrifugation, washed two times with PBS, and taken up in 100 ml sterile distilled water containing 1 mM DTT.…”
Section: Cellular Proteasome Activitymentioning
confidence: 99%
“…One possibility is that the binding of PKC to PKB may protect Thr308 but not Ser473 from being phosphorylated by PDK1. Accumulated evidence has shown that the regulation of PKB phosphorylation by PKCs, whether negatively or positively, mainly occurs at Ser473 [11,22,[36][37][38]. A putative PDK2 is believed to phosphorylate PKB at Ser473 [39].…”
Section: Discussionmentioning
confidence: 99%
“…Plus récemment, Chawla et al [37] ont démontré que les agonistes de PPAR ont des effets antiinflammatoires indépendants de ce facteur de transcription. Même si le rôle précis de PPAR dans l'inflammation reste encore à élucider, il est indubitable que ce facteur de transcription a une place centrale dans le métabolisme lipidique et l'activation du macrophage via la régulation du récepteur scavenger CD36, la capture des LDL (low density lipoproteins) oxydées et sa capacité intrinsèque de se lier à des acides gras poly-insaturés ou oxydés [38]. Il est particulièrement intéressant de noter ici que le promoteur du gène p21 WAF1/CIP1 possède justement des sites putatifs de réponse aux PPAR et il a d'ailleurs déjà été clairement montré que le promoteur de p21 WAF1/CIP1 est sensible à l'acide rétinoïque (RXR-RAR) ainsi qu'à la vitamine D3 [6,7] (Figure 3).…”
Section: Métabolisme Des Lipidesunclassified